Coating-type laminated film for forming polarizing elements
The laminated film with a cured resin layer on a biaxially stretched polyester base addresses coating defects and achieves superior flatness, enhancing the quality of coated polarizing elements for display use.
Patent Information
- Application Number
- JP2020205207
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-10
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-12-10
AI Technical Summary
Conventional base films struggle to achieve both high coating properties and film flatness when forming coated polarizing elements, leading to issues such as micro air bubbles and surface defects.
A laminated film structure with a cured resin layer formed by a curable resin composition containing (meth)acrylate and a modifier, having a surface roughness of 2.5 nm or less, and a shrinkage rate difference of 1.0% or less after heat treatment, using a biaxially stretched polyester film as the base with controlled particle content and thickness.
The laminated film minimizes coating defects and ensures excellent flatness, enabling high-quality coated polarizing elements suitable for display applications.
Smart Images

Figure 0007600658000001 
Figure 0007600658000002 
Figure 0007600658000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate film for forming a coating-type polarizing element. [Background technology]
[0002] Laminated films having a cured resin layer provided on at least one side of a base film are used in various fields such as industrial materials, optical materials, electronic component materials, and battery packaging materials (see, for example, Patent Documents 1 and 2). Polyethylene terephthalate (PET) films, which are representative polyester films, and biaxially oriented PET films in particular, are widely used as base films for laminated films because of their excellent transparency, mechanical strength, heat resistance, flexibility, and the like.
[0003] In recent years, as display panels have become thinner and more functional, the trend in technology is to make the components thinner as well. One such component is a polarizing plate. A polarizing plate is generally configured by laminating triacetyl cellulose to a polarizer via an adhesive layer, but in response to technology trends, development is being actively pursued in which a polymerizable liquid crystal composition is applied onto a substrate film to obtain a thin-film coating-type polarizing element, which is then incorporated into a display.
[0004] For example, when forming a coating-type polarizing element by coating an alignment film composition and a polymerizable liquid crystal composition on a substrate film in this order, slight coating defects such as minute air bubbles directly affect the quality of the display, so that coating defects must be minimized. In addition, since the coating-type polarizing element is incorporated into a display, the substrate film itself used is required to have a high degree of smoothness. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2019-18392 A [Patent Document 2] JP 2020-34622 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, in the past, it was difficult for general-purpose substrate films to achieve both high levels of coatability of coating-type polarizing element compositions such as alignment film compositions and polymerizable liquid crystal compositions, and film flatness. Therefore, an object of the present invention is to provide a laminated film which has few coating defects when used to form a coating-type polarizing element and yet has good flatness. [Means for solving the problem]
[0007] As a result of extensive investigations, the present inventors have found that a laminate film having a specific configuration causes few coating defects when used to form a coating-type polarizing element, and at the same time, has good flatness, and have thus completed the present invention. That is, the present invention provides the following [1] to [9]. [1] A cured resin layer (X) formed on one surface of a base film by curing a curable resin composition containing (A) a (meth)acrylate and (B) a modifier, The coating type laminate film for forming a polarizing element, wherein the cured resin layer (X) has a surface roughness (Sa) of 2.5 nm or less. [2] The laminate film for forming a coating-type polarizing element according to the above [1], wherein the absolute value of the difference in shrinkage rate (MD-TD) after heat treatment at 150° C. for 30 minutes is 1.0% or less. [3] The laminate film for forming a coating-type polarizing element according to the above [1] or [2], wherein the base film is a polyester film. [4] The laminate film for forming a coating-type polarizing element according to any one of the above [1] to [3], wherein the content of particles in the base film is 0.1% by mass or less. [5] The laminate film for forming a coating-type polarizing element according to any one of the above [1] to [4], wherein the cured resin layer (X) has a thickness of 1 μm or more and 10 μm or less. [6] The laminate film for forming a coating-type polarizing element according to any one of the above [1] to [5], wherein the thickness of the substrate film is from 12 μm to 250 μm. [7] The laminate film for forming a coating-type polarizing element according to any one of the above [1] to [6], further comprising a cured resin layer (Y) on a surface of the base film opposite to the surface on which the cured resin layer (X) is provided. [8] The laminate film for forming a coating-type polarizing element according to any one of the above [1] to [7], wherein the (B) modifier comprises at least one selected from the group consisting of a (meth)acrylic polymer and a urethane (meth)acrylate. [9] A laminate film with a coating type polarizing element, comprising: the laminate film according to any one of [1] to [8]; and a coating type polarizing element formed on the cured resin layer (X) of the laminate film. Effect of the Invention
[0008] According to the present invention, it is possible to provide a laminate film which has few coating defects when forming a coating-type polarizing element and yet has good flatness, and a laminate film with a coating-type polarizing element using the laminate film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Next, an example of an embodiment of the present invention will be described. However, the present invention is not limited to the embodiment described below.
[0010] The laminate film of the present invention is for forming a coating-type polarizing element, and comprises a base film and a cured resin layer (X) formed on one surface thereof by curing a curable resin composition containing (A) a (meth)acrylate and (B) a modifier, and the cured resin layer (X) has a surface roughness (Sa) of 2.5 nm or less. The present invention will be described below with reference to an embodiment of a laminated film.
[0011] <Laminated film> The laminated film of the present embodiment comprises a base film and a cured resin layer (X) formed on at least one surface of the base film. Each component will be described in more detail below.
[0012] [Base film] The material of the base film constituting the laminated film is not particularly limited as long as it has a film shape. For example, it may be made of paper, resin, metal, etc. Among these, it is preferable that it is made of resin from the viewpoint of mechanical strength and flexibility.
[0013] Examples of the resin substrate film include resin films formed from polymers such as polyethylene, polypropylene, cycloolefin polymer, polyester, polystyrene, acrylic resin, polycarbonate, polyurethane, triacetyl cellulose, polyvinyl chloride, polyethersulfone, polyamide, polyimide, polyamideimide, etc. In addition, as long as it is possible to form a film, it may be a mixture of these materials (polymer blend) or a composite of the structural units (copolymer).
[0014] Among the above-mentioned films, polyester films are preferable because they have excellent physical properties such as heat resistance, flatness, optical properties, and strength. The polyester films may be single-layered or multi-layered films (i.e., laminated films) having two or more layers with different properties. The polyester film is a film containing polyester as a main resin component. The polyester film may be a non-stretched film (sheet) or a stretched film. Of these, a stretched film stretched in a uniaxial or biaxial direction is preferable. Of these, a biaxially stretched film is more preferable from the viewpoint of balance of mechanical properties and flatness. Therefore, a biaxially stretched polyester film is even more preferable. More preferably, the film is a biaxially oriented polyester film roll so as to be compatible with a roll-to-roll process.
[0015] The polyester, which is the main component resin of the polyester film, may be a homopolyester or a copolymer polyester. The main component resin means a resin having the largest mass ratio among the resins constituting the polyester film, and may occupy 50 mass% or more, preferably 75 mass% or more, more preferably 90 mass% or more, and even more preferably 100 mass% of the resins constituting the polyester film.
[0016] The homopolyester is preferably one obtained by polycondensation of an aromatic dicarboxylic acid and an aliphatic glycol. Examples of the aromatic dicarboxylic acid include terephthalic acid and 2,6-naphthalenedicarboxylic acid, and terephthalic acid is preferred. Examples of the aliphatic glycol include ethylene glycol, diethylene glycol, 1,4-butanediol, and 1,4-cyclohexanedimethanol, and ethylene glycol is preferred. Representative examples of homopolyester include polyethylene terephthalate (PET) and polybutylene terephthalate (PBT).
[0017] On the other hand, when the polyester is a copolymer polyester, it may be a copolymer containing 30 mol % or less of a third component. The dicarboxylic acid component of the copolymer polyester may be one or more selected from isophthalic acid, phthalic acid, terephthalic acid, 2,6-naphthalenedicarboxylic acid, adipic acid, sebacic acid, etc., and the glycol component may be one or more selected from ethylene glycol, diethylene glycol, propylene glycol, 1,4-butanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, etc. It is preferable that the copolymer polyester contains terephthalic acid as the dicarboxylic acid, contains ethylene glycol as the glycol component, and contains a third component other than these. Among these, the base film in the laminate film of the present embodiment is preferably a polyester film containing, as a main component resin, polyethylene terephthalate, in which 60 mol % or more, preferably 80 mol % or more, is an ethylene terephthalate unit.
[0018] In the base film of the laminated film of this embodiment, particles can be blended to impart easy slippage and prevent scratches in each process. When particles are blended, the type of particles to be blended is not particularly limited as long as they are particles that can impart easy slippage, and examples thereof include inorganic particles such as silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide, and organic particles such as acrylic resin, styrene resin, urea resin, phenolic resin, epoxy resin, and benzoguanamine resin. Furthermore, in the case of a polyester film, precipitated particles obtained by precipitating and finely dispersing a part of a metal compound such as a catalyst during the polyester manufacturing process can also be used. In the present embodiment, the organic particles refer to organic compounds that have been made into particles and that maintain the particulate form even in layers or members.
[0019] On the other hand, the shape of the particles to be used is not particularly limited, and any of spherical, blocky, rod-like, flat, etc. may be used. In addition, there is no particular limit to the hardness, specific gravity, color, etc. Two or more kinds of these particles may be used in combination as necessary. The average particle size of the particles used is preferably 10 μm or less, more preferably in the range of 0.1 μm to 5 μm. By setting the average particle size in the above range, the film is given an appropriate surface roughness, and good slipping properties and smoothness can be ensured. When particles are blended, for example, it is preferable to provide a surface layer and an intermediate layer and to incorporate the particles in the surface layer. In this case, it is more preferable to form a multi-layer structure having a surface layer containing particles, an intermediate layer, and a surface layer containing particles in this order.
[0020] The content of particles in the base film is preferably 5% by mass or less, more preferably 3% by mass or less, even more preferably 1% by mass or less, even more preferably 0.5% by mass or less, even more preferably 0.1% by mass or less, even more preferably 0.05% by mass or less, and preferably 0.0003% by mass or more. By setting the content of particles within the above range, it becomes easier to impart slipperiness to the base film while ensuring the transparency of the base film. However, the base film does not have to substantially contain particles. In this specification, "substantially free of particles" means that particles are not intentionally contained, and specifically means that the particle content (particle mass concentration) is 200 ppm or less, more preferably 150 ppm or less, relative to the member or layer (here, the base film). Similar terms shown below have the same meaning. In addition, when the substrate film does not substantially contain particles or the content is small, the substrate film has high transparency, and the film has a good appearance, and the smoothness of the cured resin layer surface is likely to be high. On the other hand, the slipperiness of the laminated film may be insufficient. Therefore, in such a case, the slipperiness may be improved by blending particles in the cured resin layer, or the slipperiness may be improved by providing a slippery layer having particles as described later.
[0021] The thickness of the substrate film is preferably 12 μm or more, more preferably 20 μm or more, and is preferably 250 μm or less, more preferably 188 μm or less. When the thickness of the substrate film is within the above range, it can be suitably used in optical applications.
[0022] (Laminated structure of base film) When the base film has a laminate structure having two or more layers, preferred are a three-layer structure of B / A / C consisting of an intermediate layer A, a surface layer B, and a surface layer C, and a B / A / B consisting of an intermediate layer A and a surface layer B. When the base film has a laminate structure having two or more layers, the main component resin constituting each layer is preferably polyester as described above.
[0023] In the three-layer structure of B / A / C and B / A / B, the surface layer B and the surface layer C may contain particles to ensure ease of handling.
[0024] In the above-mentioned three-layer structures of B / A / C and B / A / B, each of the surface layers B and C may contain particles having a narrow particle size distribution and a substantially uniform average particle size (so-called monodispersity).
[0025] Surface layer B and surface layer C contain particles having an average particle size of, for example, 0.1 to 10 μm, and may contain particles having an average particle size of 0.1 to 5 μm.
[0026] The average particle size of particles can be determined by measuring the diameters of 10 or more particles using a scanning electron microscope (SEM) and taking the average value. In this case, in the case of non-spherical particles, the average value of the longest and shortest diameters can be measured as the diameter of each particle.
[0027] [Cured resin layer (X)] The cured resin layer (X) is formed by curing a curable resin composition and is provided on the substrate film. The cured resin layer may be provided on only one side of the substrate film, or on both sides. The cured resin layer (X) has a function of imparting smoothness, for example. The curable resin composition contains a component that becomes a polymer by polymerization, and specifically, may contain a polymerizable compound such as a photopolymerizable compound or a thermally polymerizable compound, but the curable resin composition preferably contains a photopolymerizable compound and is a photocurable resin composition. By using a photocurable resin composition, it is not necessary to perform heat treatment at a high temperature to cure the curable resin composition, so that the generation of impurities due to heat treatment and the occurrence of heat shrinkage can be prevented. In addition, examples of the polymerizable compound include monomers having one or more polymerizable functional groups in one molecule.
[0028] The curable resin composition of the present embodiment contains (A) a (meth)acrylate, (B) a modifier, and optionally (C) a solvent. In the curable resin composition, the component (A) is typically a photopolymerizable compound, and both the component (A) and the component (B) may be photopolymerizable compounds. In this embodiment, when the expression "(meth)acrylate" is used, it means one or both of "acrylate" and "methacrylate". When the expression "(meth)acryloyl" is used, it means one or both of "acryloyl" and "methacryloyl". When the expression "(meth)acrylic" is used, it means one or both of "acrylic" and "methacrylic", and the same applies to other similar expressions. In addition, the (meth)acryloyl group concentration of the compound having a (meth)acryloyl group used in this embodiment may be expressed as (meth)acryloyl group equivalent (g / eq). The (meth)acryloyl group equivalent is the average molecular weight per (meth)acryloyl group. For example, when a (meth)acrylate compound having a number average molecular weight of 10,000 has 10 (meth)acryloyl groups per molecule, the (meth)acryloyl group equivalent is 10,000 / 10=1,000g / eq.
[0029] (A) (Meth)acrylate The curable resin composition of the present embodiment contains (A) (meth)acrylate, which tends to improve the effect of suppressing the bleeding out of additives from the layer (cured resin layer (X)) formed by curing the curable resin composition. In addition, it tends to improve scratch resistance and adhesion to a substrate film. Specific examples of the (A) (meth)acrylate include those having an ethylenically unsaturated group such as trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, tris-2-hydroxyethyl isocyanurate tri(meth)acrylate, glycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, ditrimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, ditrimethylolpropane penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and ditrimethylolpropane hexa(meth)acrylate. Examples of the polyfunctional (meth)acrylate include polyfunctional (meth)acrylates having three or more functional groups; modified polyfunctional (meth)acrylate compounds in which a portion of these (meth)acrylates is substituted with an alkyl group or ε-caprolactone; polyfunctional (meth)acrylates having a nitrogen atom-containing heterocyclic structure, such as polyfunctional (meth)acrylates having an isocyanurate structure; polyfunctional (meth)acrylates having a multi-branched resin structure, such as polyfunctional (meth)acrylates having a dendrimer structure and polyfunctional (meth)acrylates having a hyperbranched structure; and urethane (meth)acrylates in which (meth)acrylates having hydroxyl groups, such as pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, etc., are added to polyisocyanates such as diisocyanates and triisocyanates, or trimers (isocyanurates) thereof. The (meth)acrylate having a hydroxyl group is preferably polyfunctional having two or more ethylenically unsaturated groups. The (A) (meth)acrylate preferably includes a urethane (meth)acrylate.
[0030] Specifically, the (meth)acrylate is preferably pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, or dipentaerythritol hexa(meth)acrylate from the viewpoint of compatibility with the (meth)acrylic polymer, and is more preferably pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, or pentaerythritol tri(meth)acrylate and hexamethylene diisocyanate from the viewpoint of the scratch resistance and weather resistance of the coating film and the effect of suppressing bleed-out of additives. Preferred are urethane (meth)acrylates which are reaction products of pentaerythritol tri(meth)acrylate and isophorone diisocyanate, urethane (meth)acrylates which are reaction products of dipentaerythritol penta(meth)acrylate and hexamethylene diisocyanate, urethane (meth)acrylates which are reaction products of dipentaerythritol penta(meth)acrylate and isophorone diisocyanate, and urethane (meth)acrylates which are reaction products of a mixture of dipentaerythritol penta(meth)acrylate and dipentaerythritol hexa(meth)acrylate and isophorone diisocyanate. These may be used alone or in combination of two or more.
[0031] Among the above, more preferred are trifunctional to hexafunctional polyfunctional (meth)acrylates, or urethane (meth)acrylates obtained by adding a polyfunctional (e.g., trifunctional to pentafunctional) (meth)acrylate having a hydroxyl group to a polyisocyanate, and more preferred are combinations of the above polyfunctional (meth)acrylates and urethane (meth)acrylates.More preferably, the polyisocyanate used in the urethane (meth)acrylate is a diisocyanate.
[0032] The weight average molecular weight of the (A) (meth)acrylate is, for example, 250 or more, preferably 300 or more, more preferably 400 or more, and even more preferably 500 or more, and for example, 8,000 or less, preferably 7,000 or less, more preferably 5,000 or less, and even more preferably 3,000 or less. The weight average molecular weight is a value measured by gel permeation chromatography (GPC) and calculated in terms of standard polystyrene.
[0033] The (meth)acryloyl group equivalent of the (A) (meth)acrylate is preferably 80 g / eq or more, more preferably 85 g / eq or more, even more preferably 90 g / eq or more, and is preferably less than 150 g / eq, more preferably less than 135 g / eq, even more preferably less than 120 g / eq. When the (meth)acryloyl group equivalent of the (A) (meth)acrylate is within the above range, a uniform coating film can be easily formed.
[0034] As described above, the urethane (meth)acrylate as component (A) is a reaction product between polyisocyanate or isocyanurate and (meth)acrylate having a hydroxyl group, but it may be produced by reacting polyisocyanate or isocyanurate with a mixture of (meth)acrylate having a hydroxyl group and (meth)acrylate not having a hydroxyl group. In this case, the (meth)acrylate not having a hydroxyl group remains as an unreacted product, but it is preferable to use it as component (A) by adding it as it is to the curable resin composition.
[0035] (B) Modifier The curable resin composition of the present embodiment has an advantage that, by using the (A) (meth)acrylate component and the (B) modifier in combination, the additive bleed-out suppression effect is maintained while preventing the occurrence of curling, heat wrinkles, etc., and the film flatness can be improved. In addition, the ultraviolet absorbing performance is improved, and the weather resistance is also likely to be improved. The (B) modifier is not particularly limited as long as it does not impair the object of the present invention, but it preferably contains at least one selected from a (meth)acrylic polymer and a urethane (meth)acrylate, more preferably at least one selected from a (meth)acrylic polymer and a urethane (meth)acrylate, and even more preferably is a (meth)acrylic polymer. Here, the (B) modifier has a larger molecular weight than the (A) (meth)acrylate, and since the (B) modifier has a larger molecular weight than the (A) (meth)acrylate, a modifying effect of improving the film flatness can be obtained.
[0036] The urethane (meth)acrylate used as the (B) modifier may be used as a component that modifies a curable resin composition containing the (A) component, which contains, for example, a (meth)acrylate, and it is preferable to use a component having a larger molecular weight than the (meth)acrylate as the (A) component. Therefore, when the curable resin composition contains a urethane (meth)acrylate as the (B) component, it is preferable that the curable resin composition contains a urethane (meth)acrylate as the (A) component and a urethane (meth)acrylate as the (B) component having a weight average molecular weight larger than that of the urethane (meth)acrylate of the (A) component.
[0037] ((Meth)acrylic polymer) The weight average molecular weight of the (meth)acrylic polymer used as component (B) is larger than that of the (meth)acrylate (A) and is preferably 1,000 or more, more preferably 3,000 or more, even more preferably 5,000 or more, even more preferably 10,000 or more, and is preferably 100,000 or less, more preferably 70,000 or less, even more preferably 30,000 or less.
[0038] By setting the weight average molecular weight of the (meth)acrylic polymer within the above range, the flatness of the film can be easily ensured. In addition, by setting the weight average molecular weight of the (meth)acrylic polymer to 1,000 or more, the surface hardness of the cured resin layer can be prevented from decreasing. In addition, by setting the weight average molecular weight of the (meth)acrylic polymer to 100,000 or less, the viscosity of the coating liquid can be prevented from increasing, and the smoothness of the cured resin layer can be prevented from decreasing.
[0039] The (meth)acrylic polymer is a polymer having a (meth)acrylic acid alkyl ester as a main constituent unit. Examples of the (meth)acrylic acid alkyl ester include (meth)acrylic acid chain alkyl esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, t-butyl (meth)acrylate, n-pentyl (meth)acrylate, and n-hexyl (meth)acrylate, and (meth)acrylic acid alkyl esters having a cyclic structure such as isobornyl (meth)acrylate, 4-t-butylcyclohexyl (meth)acrylate, tricyclodecanyl (meth)acrylate, dicyclopentaenyl (meth)acrylate, and adamantyl (meth)acrylate. These may be used alone or in combination of two or more. Among these, from the viewpoints of the compatibility of the (B) (meth)acrylic polymer with the (A) (meth)acrylate and the heat resistance of the cured resin layer, a chain alkyl (meth)acrylate ester is preferred, a chain alkyl (meth)acrylate ester having an alkyl group with 1 to 4 carbon atoms is more preferred, and methyl (meth)acrylate is even more preferred. That is, a polymer having methyl (meth)acrylate as a main structural unit is preferred. The (meth)acrylic polymer may also have a radically polymerizable double bond. Incidentally, the term "main structural unit" means that the structural unit is the main component in the (meth)acrylic polymer, and is contained in an amount of, for example, 50 mass % or more, preferably 70 mass % or more, and more preferably 85 mass % or more.
[0040] For the purpose of improving the glass transition temperature, mechanical properties, compatibility, etc., the (meth)acrylic polymer can be copolymerized with (meth)acrylic acid esters other than (meth)acrylic acid alkyl esters, (meth)acrylic acid, and other compounds having a vinyl group. Examples of the (meth)acrylic acid esters other than the (meth)acrylic acid alkyl esters include hydroxyalkyl (meth)acrylates such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate, alkoxyalkyl (meth)acrylates such as methoxymethyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxymethyl (meth)acrylate, and ethoxyethyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, glycidyl (meth)acrylate, and γ-butyrolactone (meth)acrylate. Examples of the compound having a vinyl group include acrylamide compounds such as dimethylacrylamide, hydroxyethylacrylamide, and dimethylaminopropylacrylamide; styrene compounds such as styrene, α-methylstyrene, and p-methoxystyrene; and maleic anhydride.
[0041] The glass transition temperature (Tg) of the (meth)acrylic polymer is preferably 60° C. or higher, more preferably 80° C. or higher, and even more preferably 90° C. or higher, from the viewpoint of improving the mechanical properties of the cured resin layer. The glass transition temperature (Tg) is preferably 140° C. or lower, more preferably 130° C. or lower, and even more preferably 120° C. or lower, from the viewpoint of improving the processability of a laminate film having the cured resin layer laminated thereon.
[0042] The glass transition temperature (Tg) can be calculated from the type and mass fraction of the monomers forming the (meth)acrylic polymer by the following Fox formula. 1 / Tg=Σ(Wi / Tgi) In the above formula, Tg is the glass transition temperature (unit: K) of the (meth)acrylic polymer, Wi is the mass fraction of the monomer unit derived from monomer i constituting the (meth)acrylic polymer, and Tgi is the glass transition temperature (unit: K) of the homopolymer of monomer i. The value of Tgi can be the value described in POLYMER HANDBOOK Volume 1 (WILEY-INTERSCIENCE).
[0043] (Urethane (meth)acrylate) The urethane (meth)acrylate used as the (B) modifier is obtained by reacting an isocyanate compound with a hydroxyl group-containing (meth)acrylate compound, or by reacting an isocyanate compound with a polyol compound with a hydroxyl group-containing (meth)acrylate compound. The urethane (meth)acrylate can be used alone or in combination of two or more kinds. When the urethane (meth)acrylate is used as the (B) modifier, the scratch resistance is improved.
[0044] Examples of the isocyanate-based compound include polyisocyanate-based compounds such as aromatic polyisocyanates, aliphatic polyisocyanates, and alicyclic polyisocyanates, and among these, diisocyanate compounds are preferred. Examples of the isocyanate-based compound include isocyanate-based compounds having an isocyanurate skeleton obtained by isocyanating a diisocyanate compound. Examples of the aromatic polyisocyanate include tolylene diisocyanate, diphenylmethane diisocyanate, polyphenylmethane polyisocyanate, modified diphenylmethane diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, phenylene diisocyanate, and naphthalene diisocyanate. Examples of the aliphatic polyisocyanates include hexamethylene diisocyanate, pentamethylene diisocyanate, trimethylhexamethylene diisocyanate, lysine diisocyanate, and lysine triisocyanate. Examples of the alicyclic polyisocyanate include hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, norbornene diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, and 1,4-bis(isocyanatomethyl)cyclohexane. Among these, aliphatic diisocyanates and alicyclic diisocyanates are preferred from the viewpoint of excellent yellowing resistance. Also, isocyanate-based compounds having an isocyanurate skeleton are preferred, and from the same viewpoint, isocyanate-based compounds having an isocyanurate skeleton obtained by isocyanating an aliphatic diisocyanate or an alicyclic diisocyanate are also preferred, and among these, isocyanate-based compounds having an isocyanurate skeleton are more preferred. The isocyanate compounds may be used alone or in combination of two or more kinds.
[0045] Examples of the hydroxyl group-containing (meth)acrylate compound include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate, 2-hydroxyethyl acryloyl phosphate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, caprolactone-modified 2-hydroxyethyl (meth)acrylate, dipropylene glycol (meth)acrylate, fatty acid-modified glycidyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, and 2-hydroxy-3-(meth)acryloyloxypropyl. Examples of the hydroxyl group-containing (meth)acrylate include monofunctional hydroxyl group-containing (meth)acrylates having one ethylenically unsaturated group such as (meth)acrylate; bifunctional hydroxyl group-containing (meth)acrylates having two ethylenically unsaturated groups such as glycerin di(meth)acrylate and 2-hydroxy-3-acryloyl-oxypropyl methacrylate; trifunctional or higher hydroxyl group-containing (meth)acrylates having three or more ethylenically unsaturated groups such as pentaerythritol tri(meth)acrylate, caprolactone-modified pentaerythritol tri(meth)acrylate, ethylene oxide-modified pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, caprolactone-modified dipentaerythritol penta(meth)acrylate, and ethylene oxide-modified dipentaerythritol penta(meth)acrylate. These can be used alone or in combination of two or more. Among these, (meth)acrylate compounds containing three or less ethylenically unsaturated groups are preferred, as they have excellent reactivity and versatility, and provide an excellent balance between the scratch resistance of the cured resin layer and the film flatness. Furthermore, polyfunctional (meth)acrylate compounds containing two or more ethylenically unsaturated groups are more preferred, and pentaerythritol tri(meth)acrylate is more preferred.
[0046] The polyol compound may be any compound having two or more hydroxyl groups (excluding the above hydroxyl group-containing (meth)acrylates).
[0047] Examples of the polyol-based compound include aliphatic polyols, alicyclic polyols, polyether-based polyols, polyester-based polyols, polycarbonate-based polyols, polyolefin-based polyols, polybutadiene-based polyols, polyisoprene-based polyols, (meth)acrylic-based polyols, and polysiloxane-based polyols.
[0048] Examples of the aliphatic polyol include ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, trimethylene glycol, dimethylolpropane, neopentyl glycol, 2,2-diethyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,4-tetramethylenediol, 1,3-tetramethylenediol, 2-methyl-1,3-trimethylenediol, 1,5-pentamethylenediol, 1 Examples of such fatty alcohols include aliphatic alcohols containing two hydroxyl groups, such as 1,6-hexamethylenediol, 3-methyl-1,5-pentamethylenediol, 2,4-diethyl-1,5-pentamethylenediol, pentaerythritol diacrylate, 1,9-nonanediol, and 2-methyl-1,8-octanediol; sugar alcohols such as xylitol and sorbitol; and aliphatic alcohols containing three or more hydroxyl groups, such as glycerin, trimethylolpropane, and trimethylolethane.
[0049] Examples of the alicyclic polyol include cyclohexanediols such as 1,4-cyclohexanediol and cyclohexyldimethanol, hydrogenated bisphenols such as hydrogenated bisphenol A, and tricyclodecane dimethanol.
[0050] Examples of polyether polyols include alkylene structure-containing polyether polyols such as polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polybutylene glycol, polypentamethylene glycol, and polyhexamethylene glycol, and random or block copolymers of these polyalkylene glycols.
[0051] Examples of polyester-based polyols include condensation polymers of polyhydric alcohols and polycarboxylic acids, ring-opening polymers of cyclic esters (lactones), and reaction products of three components: polyhydric alcohols, polycarboxylic acids, and cyclic esters.
[0052] Examples of the polyhydric alcohol include ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, trimethylene glycol, 1,4-tetramethylene diol, 1,3-tetramethylene diol, 2-methyl-1,3-trimethylene diol, 1,5-pentamethylene diol, neopentyl glycol, 1,6-hexamethylene diol, 3-methyl-1,5-pentamethylene diol, 2,4-diethyl-1,5-pentamethylene diol, glycerin, trimethylolpropane, trimethylolethane, cyclohexanediols (such as 1,4-cyclohexanediol), bisphenols (such as bisphenol A), and sugar alcohols (such as xylitol and sorbitol).
[0053] Examples of the polyvalent carboxylic acid include aliphatic dicarboxylic acids such as malonic acid, maleic acid, fumaric acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, and dodecanedioic acid; alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid; and aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, orthophthalic acid, 2,6-naphthalenedicarboxylic acid, paraphenylenedicarboxylic acid, and trimellitic acid.
[0054] Examples of the cyclic ester include propiolactone, β-methyl-δ-valerolactone, and ε-caprolactone.
[0055] Examples of the polycarbonate-based polyol include a reaction product of a polyhydric alcohol with phosgene, and a ring-opening polymer of a cyclic carbonate (such as an alkylene carbonate).
[0056] Examples of the polyhydric alcohol used in the polycarbonate-based polyol include the polyhydric alcohols exemplified in the description of the polyester-based polyol, and examples of the alkylene carbonate include ethylene carbonate, trimethylene carbonate, tetramethylene carbonate, and hexamethylene carbonate.
[0057] The polycarbonate-based polyol may be any compound having a carbonate bond in the molecule and a hydroxyl group at the end, and may have an ester bond in addition to the carbonate bond.
[0058] The polyolefin polyols include those having a homopolymer or copolymer of ethylene, propylene, butene, or the like as a saturated hydrocarbon skeleton and having hydroxyl groups at the molecular terminals.
[0059] The polybutadiene-based polyols include those having a butadiene copolymer as a hydrocarbon skeleton and having hydroxyl groups at the molecular terminals. The polybutadiene-based polyol may be a hydrogenated polybutadiene polyol in which all or a part of the ethylenically unsaturated groups contained in the structure thereof have been hydrogenated.
[0060] The polyisoprene-based polyols include those having an isoprene copolymer as a hydrocarbon backbone and having hydroxyl groups at the molecular terminals. The polyisoprene-based polyol may be a hydrogenated polyisoprene polyol in which all or a part of the ethylenically unsaturated groups contained in the structure have been hydrogenated.
[0061] The (meth)acrylic polyol may be one having at least two hydroxyl groups in the molecule of a (meth)acrylic acid ester polymer or copolymer, and examples of such (meth)acrylic acid ester include (meth)acrylic acid alkyl esters such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, and octadecyl (meth)acrylate. In addition, copolymers of (meth)acrylic acid esters and hydroxyalkyl (meth)acrylates such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate may also be used.
[0062] Examples of the polysiloxane polyol include dimethylpolysiloxane polyol and methylphenylpolysiloxane polyol.
[0063] The above polyol compounds can be used alone or in combination of two or more.
[0064] In the addition reaction of the above-mentioned isocyanate compound with a hydroxyl group-containing (meth)acrylate compound, or an isocyanate compound, a hydroxyl group-containing (meth)acrylate compound, and a polyol, the reaction is terminated when the residual isocyanate group content in the reaction system becomes 0.5 mass% or less, thereby obtaining a urethane (meth)acrylate.
[0065] When the urethane (meth)acrylate used as the (B) modifier includes one obtained by reacting an isocyanate compound, a polyol compound, and a hydroxyl group-containing (meth)acrylate compound, it is preferable to obtain the urethane (meth)acrylate by reacting a reaction product having an isocyanate group obtained by reacting an isocyanate compound with a polyol compound, or a mixture of the reaction product and an isocyanate compound, with a hydroxyl group-containing (meth)acrylate compound. The urethane (meth)acrylate used as the (B) modifier obtained by such a reaction may be a mixture of one obtained by reacting an isocyanate-based compound with a hydroxyl group-containing (meth)acrylate-based compound and one obtained by reacting an isocyanate-based compound, a polyol-based compound, and a hydroxyl group-containing (meth)acrylate-based compound.
[0066] In the reaction between an isocyanate compound and a hydroxyl group-containing (meth)acrylate compound, it is also preferable to use a catalyst for the purpose of promoting the reaction. Examples of such catalysts include organometallic compounds such as dibutyltin dilaurate, dibutyltin diacetate, trimethyltin hydroxide, tetra-n-butyltin, zinc bisacetylacetonate, zirconium tris(acetylacetonate)ethylacetoacetate, and zirconium tetraacetylacetonate; metal salts such as tin octenate, zinc hexanoate, zinc octenate, zinc stearate, zirconium 2-ethylhexanoate, cobalt naphthenate, stannous chloride, stannous chloride, and potassium acetate; triethylamine, triethylenediamine, benzyldiethylamine, 1,4-diazabicyclo[2,2,2]octane, and 1,8-diazabicyclo[5,4,0]un. Decene, N,N,N',N'-tetramethyl-1,3-butanediamine, N-methylmorpholine, N-ethylmorpholine, and other amine catalysts, bismuth nitrate, bismuth bromide, bismuth iodide, bismuth sulfide, and other organic bismuth compounds, such as dibutyl bismuth dilaurate and dioctyl bismuth dilaurate, and organic acid bismuth salts, such as bismuth 2-ethylhexanoate, bismuth naphthenate, bismuth isodecanoate, bismuth neodecanoate, bismuth laurate, bismuth maleate, bismuth stearate, bismuth oleate, bismuth linoleate, bismuth acetate, bismuth tribisneodecanoate, bismuth disalicylate, and bismuth digallate, are among the bismuth catalysts, and dibutyltin dilaurate and 1,8-diazabicyclo[5,4,0]undecene are preferred. These can be used alone or in combination of two or more.
[0067] In the reaction between an isocyanate compound and a hydroxyl group-containing (meth)acrylate compound, an organic solvent having no functional group reactive with an isocyanate group, for example, an ester such as ethyl acetate or butyl acetate, a ketone such as methyl ethyl ketone or methyl isobutyl ketone, an aromatic such as toluene or xylene, etc., can be used. A polymerization inhibitor or the like may also be used as appropriate.
[0068] In addition, the urethane (meth)acrylate as the (B) component is a reaction product of a hydroxyl group-containing (meth)acrylate compound and an isocyanate compound, or a hydroxyl group-containing (meth)acrylate compound, an isocyanate compound, and a polyol compound, but may be produced by reacting a mixture of a (meth)acrylate having a hydroxyl group and a (meth)acrylate not having a hydroxyl group with an isocyanate compound. Alternatively, it may be produced by reacting a mixture of a (meth)acrylate having a hydroxyl group and a (meth)acrylate not having a hydroxyl group with an isocyanate compound and a polyol compound. In this case, the (meth)acrylate not having a hydroxyl group remains as an unreacted product, but it is preferable to use it as the (A) component by incorporating it as it is into the curable resin composition. In the reaction between the isocyanate compound and the hydroxyl group-containing (meth)acrylate compound described above, a part or all of the isocyanate compound may be a reaction product of the isocyanate compound and a polyol compound, as described above.
[0069] The weight average molecular weight of the urethane (meth)acrylate used as the (B) modifier is larger than that of the (A) (meth)acrylate, for example, 3,000 or more, preferably 5,000 or more, more preferably 8,000 or more, and preferably 100,000 or less, more preferably 70,000 or less, and further preferably 30,000 or less. By satisfying the above range, good film flatness can be ensured by forming a cured resin layer in a laminate structure such as a laminate film.
[0070] The (meth)acryloyl group equivalent of the urethane (meth)acrylate as the (B) component should be greater than the (meth)acryloyl group equivalent of the urethane (meth)acrylate as the (A) component. The (meth)acryloyl group equivalent of the urethane (meth)acrylate as the (B) component is, for example, 120 g / eq or more, preferably 135 g / eq or more, more preferably 150 g / eq or more, and is, for example, 250 g / eq or less, preferably 220 g / eq or less, more preferably 200 g / eq or less. When the (meth)acryloyl group equivalent of the urethane (meth)acrylate as the (B) component is within the above range, good film flatness can be ensured.
[0071] The content ratio (B / A) of the (B) modifier to the (A) (meth)acrylate in the curable resin composition is preferably 3 / 97 or more, more preferably 4 / 96 or more, and is preferably 45 / 55 or less, more preferably 35 / 65 or less, and even more preferably 25 / 75 or less, in terms of mass ratio. When the content ratio (B / A) is within the above range, the film flatness and the like can be easily improved.
[0072] In addition, in the curable resin composition, the components (A) and (B) are the main components, and the total amount of the components (A) and (B) is preferably 50 mass% or more, more preferably 70 mass% or more, and more preferably 80 mass% or more, and is preferably 99 mass% or less, and more preferably 97 mass% or less, based on the total solid content of the curable resin composition.
[0073] (C) Solvent The curable resin composition may be diluted with a solvent (C) to form a coating liquid. The curable resin composition may be applied as a liquid coating liquid to a substrate film, dried, and cured to form a cured resin layer. Each component (components (A) to (B), etc.) constituting the curable resin composition may be dissolved in a solvent, or may be dispersed in a solvent. The curable resin composition contains a solvent (C), and drying and curing the coating liquid may cause wrinkles, curls, etc., but in this embodiment, the combination of the components (A) to (C) can prevent wrinkles and curls. The solvent is preferably an organic solvent. Specific examples of the organic solvent include aromatic solvents such as toluene and xylene; ketone solvents such as methyl ethyl ketone, acetone, methyl isobutyl ketone, cyclohexanone, and diisobutyl ketone; ether solvents such as diethyl ether, isopropyl ether, tetrahydrofuran, dioxane, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, propylene glycol monomethyl ether, anisole, and phenetole; ester solvents such as ethyl acetate, butyl acetate, isopropyl acetate, and ethylene glycol diacetate; amide solvents such as dimethylformamide, diethylformamide, dimethylacetamide, and N-methylpyrrolidone; cellosolve solvents such as methyl cellosolve, ethyl cellosolve, and butyl cellosolve; alcohol solvents such as methanol, ethanol, propanol, isopropanol, and butanol; and halogen solvents such as dichloromethane and chloroform. These organic solvents may be used alone or in combination of two or more. Of these organic solvents, ester-based solvents, ether-based solvents, alcohol-based solvents and ketone-based solvents are preferably used.
[0074] The amount of the organic solvent used is not particularly limited, and is appropriately determined in consideration of the coatability of the prepared curable resin composition, the viscosity and surface tension of the liquid, the compatibility of the solid content, etc. The curable resin composition is prepared as a coating liquid having a solid content concentration of preferably 15 to 80 mass%, more preferably 20 to 70 mass%, using the above-mentioned solvent. Note that the "solid content" in the curable resin composition means the components excluding the solvent, which is a volatile component, and includes not only solid components but also semi-solid and viscous liquid substances.
[0075] (D) Other ingredients Various additives may be appropriately blended into the curable resin composition as necessary within the scope of the present invention. Examples of additives that may be used in combination include photoinitiators, light stabilizers, antioxidants, antistatic agents, organic pigments, organic particles, inorganic particles, flame retardants, leveling agents, dispersants, thixotropy-imparting agents (thickeners), and defoamers.
[0076] (Photoinitiator) When the curable resin composition is a photocurable resin composition, the curable resin composition preferably contains a photoinitiator in order to improve the curability. The photoinitiator is a photopolymerization initiator, and a known one can be used. Examples of the photopolymerization initiator include a photoradical generator and a photoacid generator.
[0077] Examples of the photoradical generator include benzoin and its alkyl ethers such as benzoin, benzoin methyl ether, benzoin ethyl ether, and benzoin isopropyl ether; acetophenone, 2,2-dimethoxy-2-phenylacetophenone [e.g., trade name "Omnirad (registered trademark) 651", manufactured by IGM RESINS], 2,2-diethoxy-2-phenylacetophenone, 1,1-dichloroacetophenone, 1-hydroxycyclohexyl phenyl ketone [e.g., trade name "Omnirad (registered trademark) 184", manufactured by IGM RESINS], 2-hydroxy-2-methyl-1-phenylpropan-1-one [e.g., trade name "Omnirad (registered trademark) 1173", manufactured by IGM RESINS], 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)-2-methylpropan-1-one [e.g., trade name "Omnirad (registered trademark) 127, manufactured by IGM RESINS], and the like. alkylphenones such as 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one [e.g., trade name "Omnirad (registered trademark) 2959", manufactured by IGM RESINS], 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one [e.g., trade name "Omnirad (registered trademark) 907", manufactured by IGM RESINS], and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone; 2,4,6-trimethylbenzoyldiphenylphosphine oxide [e.g., trade name "Omnirad (registered trademark) TPO", manufactured by IGM RESINS], bis-(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide [e.g., trade name "Omnirad (registered trademark) 819", manufactured by IGM RESINS], Examples of the phosphine oxides include those manufactured by POLYMERS RESINS; anthraquinones such as 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 1-chloroanthraquinone, and 2-amylanthraquinone; benzophenone and various derivatives thereof; formic acid derivatives such as methyl benzoylformate and ethyl benzoylformate. These may be used alone or in combination of two or more.
[0078] Among these photoradical generators, from the viewpoint of the light resistance of the cured product, preferred are alkylphenones, phosphine oxides, and formic acid derivatives, more preferred are 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)-2-methylpropan-1-one, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, and methyl benzoylformate, and even more preferred are 1-hydroxycyclohexyl phenyl ketone and 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)-2-methylpropan-1-one.
[0079] As the photoacid generator, known ones can be used, among which diaryliodonium salts and triarylsulfonium salts are preferred from the viewpoints of curability, acid generation efficiency, etc. Specific examples include anion salts of di(alkyl-substituted)phenyliodonium (specifically, PF6 salts, SbF5 salts, tetrakis(perfluorophenyl)borate salts, etc.). Specific examples of anion salts of (alkyl-substituted)phenyliodonium include PF6 salts of dialkylphenyliodonium [trade name "Omniad (registered trademark) 250", manufactured by IGM RESINS]. These photoacid generators may be used alone or in combination of two or more.
[0080] The content of the photoinitiator is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 1 part by mass or more, based on 100 parts by mass of the total of the compounds having a (meth)acryloyl group in the curable resin composition, from the viewpoint of improving the curability. On the other hand, from the viewpoint of maintaining the stability of the coating liquid when the curable resin composition is made into a solution and from the viewpoint of the flatness of the cured resin layer, the content is preferably 10 parts by mass or less, more preferably 7 parts by mass or less, and even more preferably 4 parts by mass or less.
[0081] (Thickness) The thickness of the cured resin layer (X) is, for example, from 1 μm to 10 μm, preferably from 1 μm to 8 μm, and more preferably from 1 μm to 5 μm. When the thickness of the cured resin layer is equal to or greater than these lower limits, the cured resin layer can adequately protect the substrate film. Furthermore, when the thickness of the cured resin layer is equal to or less than these upper limit values, curling and heat wrinkles can be further prevented in a laminate structure having a cured resin layer such as a laminate film, and better flatness can be ensured.
[0082] The cured resin layer (X) formed by curing the curable resin composition of the present embodiment contains a (meth)acrylate as component (A), a urethane (meth)acrylate as component (B), or a (meth)acrylic resin obtained by polymerizing both of them, or a (meth)acrylic polymer as component (B) (i.e., a (meth)acrylic resin). However, any resin other than these may be used as long as it does not impair the object of the present invention. However, the cured resin layer is preferably a (meth)acrylic polymer layer whose main component resin is composed of a (meth)acrylic polymer. The main component resin means the resin having the largest mass ratio among the resins constituting the cured resin layer, and may occupy 50 mass% or more, preferably 75 mass% or more, more preferably 90 mass% or more, and even more preferably 100 mass% of the resin constituting the cured resin layer. The content of particles in the cured resin layer (X) is preferably 5% by mass or less, more preferably 3% by mass or less, even more preferably 1% by mass or less, even more preferably 0.5% by mass or less, even more preferably 0.1% by mass or less, even more preferably 0.01% by mass or less, and it is more preferable that the cured resin layer (X) does not substantially contain particles. By setting the content of particles in the cured resin layer (X) within the above range, the smoothness of the surface of the cured resin layer (X) can be increased. Here, the above-mentioned particles refer to organic particles or inorganic particles. Examples of inorganic particles include silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide, while examples of organic particles include acrylic resin, styrene resin, urea resin, phenol resin, epoxy resin, and benzoguanamine resin. The average particle size of the particles is, for example, 0.005 to 10 μm.
[0083] (Method of forming a cured resin layer) The cured resin layer can be obtained by applying a curable resin composition to the surface of a substrate film, drying the composition to form a coating layer, and curing the coating layer. Examples of a method for applying the curable resin composition include a conventionally known application method such as air doctor coating, blade coating, rod coating, bar coating, knife coating, squeeze coating, impregnation coating, reverse roll coating, transfer roll coating, gravure coating, kiss roll coating, cast coating, spray coating, curtain coating, calendar coating, and extrusion coating. The drying conditions are not particularly limited, and the drying may be performed at about room temperature or by heating, for example, at about 25 to 120° C., preferably 50 to 100° C., and more preferably 60 to 90° C. The drying time is not particularly limited as long as the (D) solvent can be sufficiently volatilized, and is, for example, about 10 seconds to 30 minutes, and preferably about 15 seconds to 10 minutes.
[0084] The curing method of the curable resin composition may be appropriately selected depending on the curing mechanism of the curable resin composition, and if the curable resin composition is a thermosetting resin composition, it may be cured by heating, and if it is a photocurable resin composition, it may be cured by irradiating it with energy rays. In the laminated film of the present embodiment, active energy rays that can be used when curing the curable resin composition include ultraviolet rays, electron beams, X-rays, infrared rays, and visible light. Among these active energy rays, ultraviolet rays and electron beams are preferred from the viewpoints of curability and prevention of resin deterioration. Of these, the curing method of the curable resin composition is preferably curing by energy ray irradiation from the viewpoints of molding time and productivity, and of preventing thermal shrinkage and thermal deterioration of each member due to heating, etc. The energy ray irradiation may be performed from either side, or from the substrate film side or the opposite side of the substrate film. When the curable resin composition is cured by ultraviolet irradiation, various ultraviolet irradiation devices can be used, and as the light source, a xenon lamp, a high-pressure mercury lamp, a metal halide lamp, an LED-UV lamp, etc. can be used. The irradiation amount of ultraviolet light (unit: mJ / cm 2 ) is usually 50 to 3,000 mJ / cm 2 From the viewpoints of the curability of the curable resin composition, the flexibility of the cured product (cured resin layer), etc., it is preferably 100 to 1,000 mJ / cm 2 From the viewpoint of the flatness of the laminated film, it is more preferably 100 to 500 mJ / cm 2 is appropriately determined depending on the reaction rate of the (meth)acryloyl group required in each curing step.
[0085] In addition, when the laminated film of the present embodiment is produced, various electron beam irradiation devices can be used when the curable resin composition is cured by electron beam irradiation. The irradiation dose (Mrad) of the electron beam is usually 0.5 to 20 Mrad, and is preferably in the range of 1 to 15 Mrad from the viewpoints of the curability of the curable resin composition, the flexibility of the cured product, and prevention of damage to the substrate, and is appropriately determined according to the reaction rate of the (meth)acryloyl group required in each curing step.
[0086] [Easy adhesive layer] The laminated film of the present embodiment may have an easy-adhesion layer on the surface of the base film. The easy-adhesion layer may be provided on one side of the base film on which the cured resin layer is provided, and the cured resin layer may be formed on the surface of the easy-adhesion layer. By providing the easy-adhesion layer, it becomes easier to adhere the cured resin layer to the base film. The easy-adhesion layer is formed, for example, from an easy-adhesion layer composition containing a binder resin and a crosslinking agent.
[0087] Examples of the binder resin include polyester resin, acrylic resin, urethane resin, polyvinyl resin such as polyvinyl alcohol, polyalkylene glycol, polyalkyleneimine, methyl cellulose, hydroxycellulose, and starches. Among these, from the viewpoint of improving adhesion with the cured resin layer, it is preferable to use polyester resin, acrylic resin, and urethane resin, and more preferably polyester resin and acrylic resin. These binder resins may be used alone or in combination of two or more. In the easy-adhesion layer composition, the content of the binder resin is, for example, 20 to 90% by mass, preferably 30 to 80% by mass, based on the solid content.
[0088] As the crosslinking agent, various known crosslinking agents can be used, for example, oxazoline compounds, melamine compounds, epoxy compounds, isocyanate compounds, carbodiimide compounds, silane coupling compounds, etc. The oxazoline compound may be an acrylic polymer having an oxazoline group, etc. Among these, melamine compounds, oxazoline compounds, and epoxy compounds are preferred. These crosslinking agents may be used alone or in combination of two or more. The content of the crosslinking agent in the adhesive layer composition is, for example, 5 to 60 mass %, preferably 10 to 50 mass %, based on the solid content.
[0089] The adhesive layer composition may contain particles for the purpose of improving blocking resistance and slippage. As the particles, those shown in the slippage layer described later can be used appropriately. However, it is preferable that the adhesive layer composition (i.e., the adhesive layer) does not substantially contain particles. By substantially not containing particles, the smoothness of the cured resin layer surface can be increased. The adhesive layer composition may further contain a component for promoting crosslinking, such as a crosslinking catalyst, etc. Furthermore, it is also possible to use a defoamer, a coatability improver, a thickener, an organic lubricant, an antistatic agent, an ultraviolet absorber, an antioxidant, a foaming agent, a dye, a pigment, etc. in combination.
[0090] The adhesive layer composition is generally preferably diluted with water, an organic solvent, or a mixture thereof, and the adhesive layer may be formed by coating the surface of the substrate film with a diluted adhesive layer composition as a coating liquid and drying the coating. The coating may be performed by a conventionally known method. The thickness of the adhesive layer is usually in the range of 0.003 to 1 μm, preferably 0.005 to 0.6 μm, and more preferably 0.01 to 0.4 μm. By making the thickness 0.003 μm or more, sufficient adhesiveness can be ensured. Also, by making the thickness 1 μm or less, deterioration of appearance and blocking are less likely to occur.
[0091] [Easy layer] The laminated film of the present embodiment may have a slippery layer. The slippery layer may be provided on the surface of the substrate film opposite to the surface on which the cured resin layer is provided. The slippery layer may be provided on the surface of the substrate film. The slippery layer of the laminated film improves the slipperiness. Therefore, as described above, even if the smoothness of the surface on which the cured resin layer of the laminated film is provided is increased, the roll winding property and handling property of the laminated film are improved.
[0092] The easy-slip layer is formed from an easy-slip layer composition containing, for example, a binder resin, a crosslinking agent, and particles. The compounds that can be used for the binder resin and the crosslinking agent are as described above for the binder resin and the crosslinking agent used in the easy-adhesion layer. The content of the binder resin in the lubrication layer composition is, for example, 20 to 90 mass %, preferably 30 to 80 mass %, based on the solid content. The content of the crosslinking agent in the lubrication layer composition is, for example, 5 to 50 mass %, preferably 10 to 40 mass %, based on the solid content.
[0093] Specific examples of particles used in the easy-slip layer include silica, alumina, kaolin, calcium carbonate, organic polymer particles, etc. Among them, silica is preferred from the viewpoint of transparency. The average particle size of the particles is preferably within the range of 0.005 to 1.0 μm, more preferably 0.01 to 0.8 μm, and even more preferably 0.01 to 0.6 μm, from the viewpoint of improving the slipperiness without impairing the surface smoothness of the polyester film. The content of the particles in the easy-slip layer composition is, for example, 1 to 20 mass %, preferably 3 to 15 mass %, based on the solid content. The particles used in the easy-slip layer may be used alone or in combination of two or more types.
[0094] The lubrication layer composition is preferably diluted with water, an organic solvent, or a mixture thereof, and the lubrication layer is preferably formed by coating the diluted lubrication layer composition on the surface of the substrate film as a coating liquid and drying it. The coating may be performed by a conventionally known method. The thickness of the slippery layer is usually in the range of 0.003 to 1 μm, preferably 0.005 to 0.6 μm, and more preferably 0.01 to 0.4 μm. By making the thickness 0.003 μm or more, the particles contained in the slippery layer can be sufficiently held and slipping properties can be imparted. In addition, by making the thickness 1 μm or less, deterioration of appearance and blocking are less likely to occur.
[0095] The surface of the base film may be coated as necessary, and the above-mentioned easy-adhesion layer and easy-slip layer may be formed by coating. The coating may be performed in-line or off-line, or a combination of both, but is preferably performed in-line. In-line coating may be performed by applying a coating to the base film in the production line of the base film. For example, when the base film is a biaxially stretched film, for example, at the stage where the longitudinal stretching is completed, a coating liquid for forming at least one of the easy-adhesion layer and the easy-slip layer may be applied, and then the coating liquid may be dried, cured, etc. in the subsequent production process of the base film.
[0096] <Annealing treatment of laminated film> In this embodiment, it is preferable to perform annealing treatment to reduce shrinkage. The annealing temperature is preferably 150 to 200°C, and more preferably 170 to 200°C.
[0097] The tension in the furnace during the annealing treatment is 12 kg / m width or less, preferably 8 kg / m width or less, and particularly preferably 6 kg / m width or less.
[0098] The annealing time is preferably 1 second to 5 minutes. The lower limit of the annealing time range is preferably 1 second or more, more preferably 10 seconds or more, and even more preferably 1 minute or more. The upper limit of the annealing time range is preferably 5 minutes or less, and more preferably 3 minutes or less. The film transport speed during the annealing treatment is preferably 10 to 300 m / min, and more preferably 5 to 200 m / min.
[0099] <Physical properties of laminated film> The laminate film of this embodiment is used as a process paper (support) for forming a coating type polarizing element, and therefore the following characteristics will be described.
[0100] (Surface roughness (Sa)) Using a surface profile measurement system (Hitachi High-Tech Science Corporation's "VertScan" (registered trademark) R5500), the surface irregularities of the cured resin layer (X) surface of the laminated film are measured by optical interferometry in an area of 237.65 μm × 178.25 μm. In order to improve the coatability of the coating type polarizing element composition, the surface roughness (Sa) of the cured resin layer (X) is 2.5 nm or less, preferably 2.0 nm or less, and more preferably 1.8 nm or less. The lower limit of the surface roughness (Sa) is preferably 0.1 nm or more, more preferably 0.5 nm or more, and more preferably 1.0 nm or more, from the viewpoint of improving the slipperiness and adhesion to the coating type polarizing element. As described above, by having a high level of surface smoothness, it is possible to form a coating type polarizing element with minimal effect on the polarization characteristics. Here, the surface roughness (Sa) is the arithmetic mean height measured in accordance with ISO25178. Factors for controlling the surface roughness (Sa) of the cured resin layer (X) of the laminated film to the above upper limit or less include, for example, the content of particles contained in the base film, the easy-adhesion layer, and the cured resin layer (X). By reducing the content of particles contained in these layers, it is possible to control the surface roughness (Sa) of the cured resin layer (X) to the above upper limit or less.
[0101] (Heat shrinkage rate) The difference (absolute value) in shrinkage rate between MD and TD of the laminated film after heat treatment for 30 minutes in an atmosphere of 150° C. is preferably 1.0% or less, more preferably 0.5% or less, even more preferably 0.2% or less, and even more preferably 0.1% or less. By setting the heat shrinkage value to the above upper limit or less, better flatness can be ensured and a coatable polarizing element having good polarization properties can be formed.
[0102] <Coating-type polarizing element> The coating-type polarizing element in this embodiment refers to a cured product of a polymerizable liquid crystal composition (hereinafter, sometimes referred to as an "optically anisotropic composition") containing a polymerizable liquid crystal compound, and a laminate containing the cured product. The cured product of the optically anisotropic composition is usually obtained by coating an optically anisotropic composition containing a polymerizable liquid crystal compound and the like on an alignment film formed on a substrate, and polymerizing the polymerizable liquid crystal compound in an aligned state.
[0103] Methods for orienting a polymerizable liquid crystal compound include a method using an orientation restricting force by an orientation film provided on a substrate film, an orientation restricting force by an external field such as an electric field or a magnetic field, and / or a shear force during coating. In particular, a method using an orientation film is preferred from the viewpoint of obtaining a coatable polarizing element that has good optical performance by bringing the polymerizable liquid crystal compound into a highly ordered oriented state. The alignment film provided on the substrate film is a layer having an alignment regulating force for aligning a polymerizable liquid crystal compound described later in a desired direction. The alignment film preferably has solvent resistance for preventing dissolution when the optically anisotropic composition solution is applied, appropriate solution affinity for preventing repelling the optically anisotropic composition solution, and heat resistance during drying of the solvent or heat treatment for liquid crystal alignment. In order to control the alignment direction, the alignment film may be subjected to an alignment treatment by a known method (rubbing method, method of forming grooves (fine groove structure) on the alignment film surface, method using polarized ultraviolet light and polarized laser (photoalignment method), alignment method by LB film formation, alignment method by oblique deposition of inorganic material, etc.) described on pages 226 to 239 of "Liquid Crystal Handbook" (Maruzen Co., Ltd., published October 30, 2000). In particular, the rubbing method and photoalignment method are preferred from the viewpoint of easily achieving a high degree of alignment. The thickness of the alignment film is usually 10 nm to 1000 nm, and preferably 50 nm to 800 nm. When the thickness is within this range, it is possible to achieve both an alignment control force sufficient to align the polymerizable liquid crystal compound and a thin film.
[0104] The optically anisotropic composition is a composition containing, in addition to a polymerizable liquid crystal compound and a photopolymerization initiator, a polymerization initiator, and, if necessary, various additives and solvents such as a non-polymerizable liquid crystal compound, a polymerization inhibitor, a polymerization aid, a polymerizable non-liquid crystal compound, a non-polymerizable non-liquid crystal compound, a surfactant, a leveling agent, a coupling agent, a pH adjuster, a dispersant, an antioxidant, an organic / inorganic filler, and a metal oxide, and a cured layer of this optically anisotropic composition exhibits the optical function as a polarizing element. When the polarizing element is a polarizing film, it is preferable that the optically anisotropic composition contains a dichroic dye. Examples of the dichroic dye include iodine and dichroic organic dyes. The dichroic dye used may be one type or a combination of different dyes. The dichroic organic dye is not particularly limited, and examples thereof include azo dyes, quinone dyes (including naphthoquinone dyes, anthraquinone dyes, etc.), stilbene dyes, cyanine dyes, phthalocyanine dyes, indigo dyes, condensed polycyclic dyes (including perylene dyes, oxazine dyes, acridine dyes, etc.), etc. Among these dyes, azo dyes are preferred because they have a large molecular long / short axis ratio and can exhibit good dichroism.
[0105] The polymerizable liquid crystal compound is a liquid crystal compound having a polymerizable functional group, and the alignment is fixed by crosslinking the polymerizable functional group in the state where the liquid crystal is aligned, thereby exhibiting optical anisotropy. The polymerizable liquid crystal compound may be one type, or a combination of multiple compounds having different structures may be used. The polymerizable liquid crystal compound may be either a low molecular weight liquid crystal compound having a polymerizable functional group or a high molecular weight liquid crystal compound having a polymerizable functional group. Among them, the low molecular weight liquid crystal compound is preferred because the polymerizable liquid crystal compound tends to easily give a cured product exhibiting high alignment. The liquid crystal phase exhibited by the polymerizable liquid crystal compound can be appropriately selected from nematic liquid crystal, smectic liquid crystal, cholesteric liquid crystal, discotic liquid crystal, etc., but from the viewpoints of ease of production and obtaining a highly ordered orientation state, it is preferable for the compound to exhibit nematic liquid crystal or smectic liquid crystal. The polymerizable functional group is preferably a photopolymerizable group because of the ease of fixing the orientation structure.Specific examples include acryloyl group, methacryloyl group, acryloyloxy group, methacryloyloxy group, acryloylamino group, methacryloylamino group, vinyl group, vinyloxy group, ethynyl group, ethynyloxy group, 1,3-butadienyl group, 1,3-butadienyloxy group, oxiranyl group, oxetanyl group, glycidyl group, glycidyloxy group, styryl group, styryloxy group, etc.Among these, (meth)acryloyl group is preferable.
[0106] As the polymerizable liquid crystal compound, a liquid crystal compound having a polymerizable group can be used without being particularly limited in molecular structure. For example, as the polymerizable liquid crystal compound contained in the composition for forming an anisotropic dye film of the present embodiment, a compound represented by the following formula (1) (hereinafter, sometimes referred to as "polymerizable liquid crystal compound (1)") can be mentioned.
[0107] Q 1 -R 1 -A 11 -Y 1 -A 12 -(Y 2 -A 13 ) k -R 2 -Q 2 (1)
[0108] (In formula (1), -Q 1 represents a hydrogen atom or a polymerizable group; -Q 2 represents a polymerizable group; -R 1 -and-R 2 Each - independently represents a chain organic group; -A 11 -and-A 13 Each - independently represents a partial structure represented by the following formula (2), a divalent organic group, or a single bond: -A 12 - represents a partial structure represented by the following formula (2) or a divalent organic group; -Y 1 - and -Y 2 - each independently represents a single bond, -C(=O)O-, -OC(=O)-, -C(=S)O-, -OC(=S)-, -C(=O)S-, -SC(=O)-, or -CH 2 CH 2 -, -CH=CH-, -C≡C-, -C(=O)NH-, -NHC(=O)-, -CH 2 O-, -OCH 2 -, -CH 2 S- or -SCH 2 - stands for; -A 11 -and-A 13One of - is a partial structure represented by the following formula (2) or a divalent organic group: k is 1 or 2. If k is 2, then two -Y 2 -A 13 - may be the same or different.)
[0109] -C y -X 2 -C≡CX 1 - (2) (In formula (2), -C y - represents a hydrocarbon ring group or a heterocyclic group; -X 1 - stands for -C(=O)O-, -OC(=O)-, -C(=S)O-, -OC(=S)-, -C(=O)S-, -SC(=O)-, -CH 2 CH 2 -, -CH=CH-, -C(=O)NH-, -NHC(=O)-, -CH 2 O-, -OCH 2 -, -CH 2 S- or -SCH 2 - stands for; -X 2 - is a single bond, -C(=O)O-, -OC(=O)-, -C(=S)O-, -OC(=S)-, -C(=O)S-, -SC(=O)-, -CH 2 CH 2 -, -CH=CH-, -C(=O)NH-, -NHC(=O)-, -CH 2 O-, -OCH 2 -, -CH 2 S- or -SCH 2 - stands for
[0110] In addition, -A 11 When - is a partial structure represented by formula (2), formula (1) may be the following formula (1A) or the following formula (1B). Q 1 -R 1 -C y -X 2 -C≡CX 1 -Y 1 -A 12 -(Y 2 -A13 ) k -R 2 -Q 2 (1A) Q 1 -R 1 -X 1 -C≡CX 2 -C y -Y 1 -A 12 -(Y 2 -A 13 ) k -R 2 -Q 2 (1B)
[0111] Also, -A 12 When - is a partial structure represented by formula (2), formula (1) may be the following formula (1C) or the following formula (1D). Q 1 -R 1 -A 11 -Y 1 -C y -X 2 -C≡CX 1 -(Y 2 -A 13 ) k -R 2 -Q 2 (1C) Q 1 -R 1 -A 11 -Y 1 -X 1 -C≡CX 2 -C y -(Y 2 -A 13 ) k -R 2 -Q 2 (1D)
[0112] Also, -A 13 When - is a partial structure represented by formula (2), formula (1) may be the following formula (1E) or the following formula (1F). Q 1 -R 1 -A 11 -Y 1 -A 12 -(Y 2 -Cy -X 2 -C≡CX 1 ) k -R 2 -Q 2 (1E) Q 1 -R 1 -A 11 -Y 1 -A 12 -(Y 2 -X 1 -C≡CX 2 -C y ) k -R 2 -Q 2 (1F)
[0113] Similarly, -A 11 -, -A 12 - and -A 13 When two or more of the - are partial structures represented by formula (2), the orientation of each partial structure represented by formula (2) may be inverted.
[0114] Also, as mentioned above, -A 11 -, -A 12 - and -A 13 Each - is independently a partial structure represented by formula (2) or a divalent organic group, and -A 11 -and-A 13 - may be a single bond, but -A 11 -and-A 13 -, but neither of them are single bonds.
[0115] As the polymerizable liquid crystal compound (1), a compound represented by the above formula (1A), (1B), (1E) or (1F) is preferable because it tends to provide high alignment.
[0116] The thickness of the cured film of the optically anisotropic composition is preferably 100 nm or more, more preferably 300 nm or more, and even more preferably 1 μm or more, from the viewpoint of ensuring optical functions. On the other hand, the upper limit of the thickness is preferably 50 μm or less, more preferably 10 μm or less, and even more preferably 5 μm or less, from the viewpoint of contributing to thinner image display devices.
[0117] <Other embodiments> The laminated film of this embodiment may further comprise a cured resin layer (Y) on the surface of the base film opposite to the surface on which the cured resin layer (X) is provided. By further comprising the cured resin layer (Y), shrinkage of the laminated film can be suppressed and flatness can be further improved. Examples of the cured resin layer (Y) include the same as the cured resin layer (X) described above. Moreover, the laminate film with a coating type polarizing element of the present embodiment includes the laminate film of the present embodiment and a coating type polarizing element formed on the cured resin layer (X) of the laminate film. Examples of the configuration of the laminate film with a coating type polarizing element in this embodiment include coating type polarizing element / cured resin layer (X) / substrate film, coating type polarizing element / cured resin layer (X) / easy adhesion layer / substrate film, coating type polarizing element / cured resin layer (X) / substrate film / easy slip layer, coating type polarizing element / cured resin layer (X) / substrate film / cured resin layer (Y), coating type polarizing element / cured resin layer (X) / easy adhesion layer / substrate film / cured resin layer (Y), coating type polarizing element / cured resin layer (X) / substrate film / easy adhesion layer / cured resin layer (Y), coating type polarizing element / cured resin layer (X) / easy adhesion layer ...Z) / cured resin layer (X) / substrate film, and the like. The cured resin layer (Z) refers to a functional layer provided between the coating type polarizing element and the cured resin layer (X). If necessary, various functions such as antistatic, easy adhesion, and leveling can be imparted to the layer.
[0118] <Explanation of terms, etc.> In this embodiment, the term "film" includes the term "sheet", and the term "sheet" includes the term "film". In this embodiment, when it is written "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably larger than X" or "preferably smaller than Y". In addition, when it is stated that the amount is "X or more" (X is any number), it also means that the amount is "preferably greater than X" unless otherwise specified, and when it is stated that the amount is "Y or less" (Y is any number), it also means that the amount is "preferably smaller than Y" unless otherwise specified. EXAMPLES
[0119] The present invention will now be described in more detail with reference to examples, although the present invention is not limited to the examples described below.
[0120] <Evaluation method> The methods for measuring and evaluating various physical properties and characteristics are as follows.
[0121] (1) Intrinsic viscosity (IV) 1 g of polyester was precisely weighed, dissolved in 100 ml of a mixed solvent of phenol / tetrachloroethane = 50 / 50 (mass ratio), and measured at 30°C.
[0122] (2) Average particle size The powder was observed using a scanning electron microscope (HITACHI, "S3400N"). The diameters of 10 particles were measured from the obtained image data, and the average value of the diameters of the 10 particles was taken as the average particle size.
[0123] (3) Number average molecular weight (Mn) and weight average molecular weight (Mw) Measurement was performed using a gel permeation chromatography (GPC) "HLC-8120" (manufactured by Tosoh Corporation). As the column, TSKgel G5000HXL*GMHXL-L (manufactured by Tosoh Corporation) was used. In addition, a calibration curve was created using F288 / F80 / F40 / F10 / F4 / F1 / A5000 / A1000 / A500 (manufactured by Tosoh Corporation) and styrene as standard polystyrene. Measurement was performed at a column oven temperature of 40°C using 100 μL of a solution in which the polymer was dissolved in tetrahydrofuran to a concentration of 0.4% by mass. The number average molecular weight (Mn) and weight average molecular weight (Mw) were calculated in terms of standard polystyrene.
[0124] (4) Surface roughness of the cured resin layer (Sa) In accordance with ISO25178, the surface irregularities in an area of 237.65 μm × 178.25 μm on the cured resin layer surface of the laminated film were measured by optical interference using a surface profile measurement system (Hitachi High-Tech Science Corporation's "VertScan" (registered trademark) R5500), and the data was read and the surface roughness (Sa) of the cured resin layer surface was calculated under the following conditions. The magnification of the objective lens during the measurement was set to 20 times. (Correction conditions) Compensation: Full Baseline correction: Surface correction (polynomial approximation of the fourth degree)
[0125] (5) Shrinkage rate of laminated film A test piece measuring 15 cm x 1.5 cm was cut out from the laminated film obtained in the Examples and Comparative Examples, and a 10 cm long marked line was drawn in the center of the test piece parallel to the long side direction (the direction of measurement).Then, the test piece with the marked line drawn was heated for 30 minutes in a hot air oven maintained at 150°C in a tensionless state, and the length between the marked lines before and after the treatment was measured, and the shrinkage rate was calculated by the following formula. From the obtained shrinkage rates, the absolute value of the shrinkage rate difference (MD-TD) was calculated. Shrinkage rate (%) = {(L 0 -L 1 ) / L 0}×100 (In the above formula, L 0 is the gauge length before heat treatment, L 1 indicates the gauge length after heat treatment.) The gauge length of the laminated film was measured at five points in each of the machine direction (MD) and the transverse direction (TD) of the film, and the average value in each direction was calculated. The absolute value of the shrinkage difference (MD-TD) was calculated from the obtained shrinkage in the MD direction and the shrinkage in the TD direction.
[0126] (6) Evaluation of Coating Properties of Coating-Type Polarizing Element Composition A photoalignment film composition and a polymerizable liquid crystal composition having the following compositions were successively applied to the surface of the cured resin layer (X) of the laminated film, and cured to form a coating type polarizing element.
[0127] (Preparation of Photo-Alignment Film Composition) A photosensitive polymer represented by the following formula (Sigma-Aldrich Japan, polyvinyl cinnamate) (2 parts by mass), cyclopentanone (98 parts by mass), and a leveling agent (BYK-361N, BYK Japan K.K.) (0.02 parts by mass) were uniformly mixed to obtain a photoalignment film composition. [ka]
[0128] (Preparation of Polymerizable Liquid Crystal Composition) A polymerizable liquid crystal composition was obtained by uniformly mixing 30 parts by mass of a polymerizable liquid crystal represented by the following formula (2-methyl-1,4-phenylenebis(4-(((4-(acryloxy)butoxy)carbonyl)oxy)benzoate) manufactured by Ambeed Chemical Industries, Ltd.), 70 parts by mass of toluene, 0.3 parts by mass of a photopolymerization initiator (OMNIRAD907 manufactured by IGM Resins, Ltd.), and 0.03 parts by mass of a leveling agent (BYK-361N manufactured by BYK Japan KK). [ka]
[0129] (Preparation of laminated film with coating type polarizing element) A photoalignment film composition was applied to the surface (smooth surface) of the cured resin layer (X) of the laminated film using a bar coater so that the thickness after drying would be 0.5 μm. The applied surface was irradiated with ultraviolet light (accumulated light amount of 250 mJ / cm 2 ) through a broadband wire grid polarizer. 2 ) to obtain a film having a photo-alignment layer having an alignment control force. A polymerizable liquid crystal composition was applied to the photoalignment layer-formed surface of the film using a bar coater to a thickness (after drying) of 2 μm, heated at 80° C. for 2 minutes, cooled to room temperature, and then irradiated with ultraviolet light (500 mJ / cm 2 in cumulative light amount). 2) to form a coating type polarizing element, and a film with a coating type polarizing element was obtained. The appearance of the obtained coating-type polarizing element-attached film was evaluated as follows. (Judgment criteria) ◯: There is no coating defect, or even if there is a defect, it is very small. ×: Coating defects are clearly observed.
[0130] The materials of the laminated films in the respective Examples and Comparative Examples are as follows. (Base film with easy-adhesion layer) ·PET film F1: PET film with easy-adhesive layer, PET film thickness: 38μm The PET film F1 was produced by the following method. First, polyester A was prepared, which was a polyester having a dicarboxylic acid component of terephthalic acid and an alcohol component of 98 mol % of ethylene glycol and 2 mol % of diethylene glycol, and had an intrinsic viscosity (IV) of 0.64 dl / g. In addition, polyester composition B was prepared, which contained a polyester whose dicarboxylic acid component was terephthalic acid, whose alcohol components were 98 mol % ethylene glycol and 2 mol % diethylene glycol, and whose intrinsic viscosity (IV) was 0.62 dl / g, and 0.2 mass % of silica particles having an average particle size of 3 μm. Next, as the intermediate layer, polyester A was fed into a main vented twin-screw extruder set at 280° C. As the surface layer, chips of a polyester composition containing 50% by mass of polyester A and 50% by mass of polyester composition B were fed into a sub vented twin-screw extruder set at 280° C. The polymer from the main extruder was the intermediate layer, and the polymer from the sub-extruder was the surface layer. The two-type, three-layer structure (surface layer / intermediate layer / surface layer=1:8:1 discharge amount (mass ratio)) was co-extruded from the die, and the surface temperature was set to 30°C using the electrostatic application adhesion method, and the resulting unstretched sheet was rapidly solidified on a cooling roll with an electrostatic application adhesion method. The unstretched sheet was then stretched 3.5 times in the longitudinal direction (MD) at 85°C, introduced into a tenter, and coated with an easy-adhesion layer composed of the following easy-adhesion layer composition so that the thickness (after drying) was 0.1 μm. The sheet was then stretched 4.4 times in the transverse direction (TD) at 100°C, and then heat-treated at 200°C for 10 seconds to obtain a PET film F1 with a thickness of 38 μm.
[0131] (Formulation conditions of adhesive layer composition) The following compounds were mixed in the ratio X1:X2:Y1:Y2:Y3 = 60:10:10:10:10 (mass % solids). (binder resin) (X1): Aqueous dispersion of a polyester resin having a condensed polycyclic structure copolymerized with the following composition: Monomer composition: (acid component) 2,6-naphthalenedicarboxylic acid / 5-sodium sulfoisophthalic acid / (diol component) ethylene glycol / diethylene glycol = 92 / 8 / / 80 / 20 (mol%) (X2): Aqueous dispersion of acrylic resin polymerized with the following composition: Emulsion polymer of ethyl acrylate / n-butyl acrylate / methyl methacrylate / N-methylolacrylamide / acrylic acid = 65 / 21 / 10 / 2 / 2 (mass%) (emulsifier: anionic surfactant) (Crosslinking agent) (Y1): Hexamethoxymethylol melamine (Y2): Water-soluble polyglycerol polyglycidyl ether (Y3): Oxazoline group-containing acrylic polymer (Epocross (registered trademark), oxazoline group amount 4.5 mmol / g, manufactured by Nippon Shokubai Co., Ltd.)
[0132] ·PET film F2: PET film with easy-adhesive layer, PET film thickness: 25μm PET film F2 having a thickness of 25 μm and provided with an easy-adhesion layer was obtained in the same manner as PET film F1, except that the thickness of the PET film was changed to 25 μm.
[0133] (Curable resin composition) (A1) Urethane (meth)acrylate Manufacturing Example A four-neck flask equipped with a thermometer, a stirrer, a water-cooled condenser, and a nitrogen gas inlet was charged with 66 parts by mass of isophorone diisocyanate (a1-1), 94 parts by mass of a mixture (a1-2) of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate having a hydroxyl value of 50 mgKOH / g (a1-1 / a1-2=0.28 / 0.72 (mol / mol)), 0.6 parts by mass of 2,6-di-tert-butylcresol as a polymerization inhibitor, and 0.05 parts by mass of dibutyltin dilaurate as a reaction catalyst, and reacted at 60° C. until the residual isocyanate group reached 0.3%, yielding a urethane (meth)acrylate composition (A1) with an acryloyl equivalent of 107 g / eq. The resulting urethane (meth)acrylate composition (A1) had a weight average molecular weight of 1,600 and a viscosity at 60°C of 1,500 mPa·s.
[0134] (A2) Pentaerythritol tetraacrylate (A-TMMT: manufactured by Shin-Nakamura Chemical Co., Ltd.) Viscosity: 215mPa·s / 40℃
[0135] (B1) (Meth)acrylic polymer: (BR87, manufactured by Mitsubishi Chemical Corporation) MMA copolymer (polymer whose main structural unit is methyl methacrylate) with a weight average molecular weight (Mw) of 25,000, an acid value of 9.8 mgKOH / g, and a glass transition temperature (Tg) of 106°C. (C) Solvent A mixed solvent of methyl ethyl ketone (MEK) and propylene glycol monomethyl ether (PGM) (mixed so that the solvent ratio of MEK to PGM in the coating liquid is 3:7) (D1) Photoinitiator IGM Resins, Omnirad127 (D2) Leveling agent Polyflow 75 (acrylic polymer: manufactured by Kyoeisha Chemical Co., Ltd.) (D3) Nanosilica particles SIRMIBK15WT%-B04 (CIK Nanotech Co., Ltd.)
[0136] [Example 1] The following curable resin composition (X1) was applied by bar coating onto the easy-adhesion layer of the PET film F1 so that the thickness (after curing) was 4.5 μm, and the composition was dried at 80° C. for 30 seconds, and then irradiated with ultraviolet light (integrated light amount of 200 mJ / cm 2 Next, the following curable resin composition (Y) was applied by bar coating to the surface of the PET film F1 opposite to the surface on which the cured resin layer (X) was formed so that the thickness (after curing) was 4.5 μm, and the applied surface was dried at 80° C. for 30 seconds, and then irradiated with ultraviolet light (integrated light amount of 200 mJ / cm 2 ) to form a cured resin layer (Y1). The resulting laminated film was evaluated, and the evaluation results are shown in Table 1. (Formulation conditions of curable resin composition (X1)) A1 / B1 / C / D1 / D2=100 / 5 / 325 / 3 / 0.48 (mass parts) (Formulation conditions of curable resin composition (Y1)) A1 / A2 / B1 / C / D1 / D3=80 / 20 / 3 / 342 / 3 / 8 (mass parts)
[0137] [Example 2] The following curable resin composition (X2) was applied by bar coating onto the easy-adhesion layer of the PET film F1 so that the thickness (after curing) was 3.0 μm, and the composition was dried at 80° C. for 30 seconds, and then irradiated with ultraviolet light (integrated light amount of 200 mJ / cm 2 ) to form a cured resin layer (X2). The resulting laminated film was evaluated, and the evaluation results are shown in Table 1. (Blending conditions of curable resin composition (X2)) A1 / B1 / C / D1 / D2=100 / 5 / 325 / 3 / 0.48 (mass parts)
[0138] [Comparative Example 1] The following curable resin composition (X3) was applied by bar coating onto the easy-adhesion layer of the PET film F2 so that the thickness (after curing) was 1.5 μm, and the composition was dried at 80° C. for 30 seconds, and then irradiated with ultraviolet light (integrated light amount of 200 mJ / cm 2 ) to form a cured resin layer (X3). The resulting laminated film was evaluated, and the evaluation results are shown in Table 1. (Formulation conditions of curable resin composition (X3)) A1 / A2 / B1 / C / D1 / D3=80 / 20 / 3 / 342 / 3 / 8 (mass parts)
[0139] [Table 1]
[0140] (Consideration) In Examples 1 and 2, after coating the coating-type polarizing element compositions such as the photoalignment film composition and the polymerizable liquid crystal composition, the appearance of the obtained coating-type polarizing element was generally better than that of Comparative Example 1. That is, the laminate films of Examples 1 and 2 had no coating defects when forming the coating-type polarizing element, and furthermore, due to the low difference in shrinkage rate, curling, heat wrinkles, etc. were unlikely to occur, and the flatness was excellent. In addition, the smoothness level of the surface of the conventional substrate film in Comparative Example 1 is at a level that can be used without any problems, but it is difficult to apply it to the formation of a coating-type polarizing element because a particularly high level of smoothness is required. Furthermore, the substrate film needs to have a high level of good flatness so that it can be applied to a roll-to-roll process. This is because there is a concern that minute irregularities on the film surface or slight dimensional changes in the film may affect the performance (particularly the polarization characteristics) of the coating-type polarizing element.
Claims
1. The present invention has a configuration in which a cured resin layer (X) is provided on one surface of a base film, the cured resin layer (X) being obtained by curing a curable resin composition containing (A) a (meth)acrylate and (B) a modifier, The (B) modifier is a (meth)acrylic polymer, The cured resin layer (X) has a surface roughness (Sa) of 2.5 nm or less.
2. 2. The laminate film for forming a coating-type polarizing element according to claim 1, wherein the absolute value of the difference in shrinkage rate (MD-TD) after heat treatment at 150° C. for 30 minutes is 1.0% or less.
3. 3. The laminate film for forming a coating-type polarizing element according to claim 1, wherein the substrate film is a polyester film.
4. 4. The laminate film for forming a coating-type polarizing element according to claim 1, wherein the content of particles in the base film is 0.1% by mass or less.
5. 5. The laminate film for forming a coating type polarizing element according to claim 1, wherein the cured resin layer (X) has a thickness of 1 μm or more and 10 μm or less.
6. 6. The laminate film for forming a coating-type polarizing element according to claim 1, wherein the thickness of the substrate film is from 12 μm to 250 μm.
7. The laminate film for forming a coating-type polarizing element according to any one of claims 1 to 6, further comprising a cured resin layer (Y) on a surface of the base film opposite to the surface on which the cured resin layer (X) is provided.
8. A laminated film with a coating type polarizing element, comprising: the laminated film according to any one of claims 1 to 7; and a coating type polarizing element formed on the cured resin layer (X) of the laminated film.
Citation Information
Patent Citations
Laminated polyester film for optical tape
JP1994068521A
Laminated film and transparent substrate
JP2015217667A
Hard coat film
JP2016108568A
Function transferring plastic film
JP2019018392A
Aligned liquid crystal film and production method of the same, optical film with adhesive and production method of the same, and image display device
JP2020034622A
